Development of Hanzi Radical Learning Media Xīnzìpáng for Students - Parmawati, Vitrianti Della; Pamuji, Dian Yuni; Marsuki, Ria Riski; Agwinanda , Almira (Universitas Negeri Semarang, 2024)
This research was conducted based on the results of observations which showed that hanzi learning media for Chinese Language Education students at Semarang State University needed the development of creative and innovative hanzi learning media. The objectives of this research are 1) to describe the results of the needs analysis of radical hanzi learning media